Effectiveness of Teaching and Text Message Based Intervention on Dietary Habits among Overweight Adolescents in Selected Schools of Ambala, Haryana (Medico Legal Update, 2021)
Background: Overweight and obesity is associated with an increased risk of morbidity and mortality aswell as reduced life expectancy.Objectives: The objectives of the study was to assess and compare the dietary habits among overweightadolescents before and after teaching and text message based intervention in experimental and comparisongroup, to determine the association of dietary habits among overweight adolescents with their selectedvariables in experimental and comparison group.Methodology: A quasi experimental non equivalent control group pretest-posttest design was used for thestudy. Fifty nine (59) overweight adolescents were selected by using purposive sampling technique. Thedata was collected by rating scale to assess the dietary habits for overweight.Results and Conclusion: The findings revealed that mean post test score of dietary habits (29.5 ± 2.55) wassignificantly higher in experimental group than mean post test score of dietary habits. There was a significantassociation found between post test of dietary habits of experimental group with BMI (p=0.02) and withage (p=0.05) in comparison group. It was concluded from the study that teaching and text message basedintervention was effective in improving the dietary habits among overweight adolescents.